2022
DOI: 10.1037/aca0000501
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of integrated arts-based groups to people with mental health conditions and community members: Processes and outcomes.

Abstract: The two major challenges facing people with mental health conditions (MHCs) are stigma and discrimination. This study focused on the Amitim program’s nationwide integrated arts-based groups that not only aim to impart knowledge and skills in the arts (e.g., theater, writing, music, poetry, visual art, etc.) but also reduce public and self-stigma, and promote personal recovery. This study, composed of a sample of 642 Israeli adults, examined whether people with MHCs and nonclinical community members who attende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 108 publications
0
1
0
Order By: Relevance
“…Research has found that self‐awareness allows an individual to adjust their perceptions and challenge internalised stigma, enabling a positive identity change to occur as self‐concepts become more congruent (Illeris, 2014; Mezirow, 2018). Arts activities may be particularly effective in developing self‐awareness as creativity and imagination have been found to play an important role in self‐efficacy and transformative learning (Baker et al, 2016; Boyd, 1994; Dirkx, 1998; Montgomery et al, 2008; Nitzan & Orkibi, 2022). Furthermore, brain imaging research has revealed that reappraisal tasks using an artistic approach activate the left caudate nucleus (parts of the reward system), which is under‐utilised within an SMI population (Baker et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Research has found that self‐awareness allows an individual to adjust their perceptions and challenge internalised stigma, enabling a positive identity change to occur as self‐concepts become more congruent (Illeris, 2014; Mezirow, 2018). Arts activities may be particularly effective in developing self‐awareness as creativity and imagination have been found to play an important role in self‐efficacy and transformative learning (Baker et al, 2016; Boyd, 1994; Dirkx, 1998; Montgomery et al, 2008; Nitzan & Orkibi, 2022). Furthermore, brain imaging research has revealed that reappraisal tasks using an artistic approach activate the left caudate nucleus (parts of the reward system), which is under‐utilised within an SMI population (Baker et al, 2016).…”
Section: Discussionmentioning
confidence: 99%